Improving the chemotherapy process and service to cancer patients - Garcia-Alonso A (Dove Medical Press, 2011)
A Garcia-AlonsoNorth Wales Cancer Treatment Centre, Glan Clwyd Hospital, Bodelwyddan, Wales, United KingdomAbstract: The North Wales Cancer Treatment Centre (NWCTC) has to deal with an increasing demand in the number of patients who require chemotherapy, with the escalating use of second line, third line, and additional treatment for many cancers. As a result, there is growing pressure on the chemotherapy unit to deliver treatment quickly, efficiently, and safely. Following guidelines from the Department of Health's Manual for Cancer Services, we are constantly looking for ways to improve and develop the level of care provided at our center, and the process of receiving chemotherapy has been identified as an area of high risk. Therefore, a team was established to review and explore current practices at the NWCTC with the goal of implementing an improved process to minimize the risks of chemotherapy treatment.Keywords: chemotherapy, modernization tools, referral forms, chemotherapy day unit